Determination techniques of Archie's parameters: A, m and n in heterogeneous reservoirs - Mohamad, A.M. (Institute of Physics Publishing, 2017)
The determination of water saturation in a heterogeneous reservoir is becoming more challenging, as Archie's equation is only suitable for clean homogeneous formation and Archie's parameters are highly dependent on the properties of the rock. This study focuses on the measurement of Archie's parameters in carbonate and sandstone core samples around Malaysian heterogeneous carbonate and sandstone reservoirs. Three techniques for the determination of Archie's parameters a, m and n will be implemented: the conventional technique, core Archie parameter estimation (CAPE) and the three-dimensional regression technique (3D). By using the results obtained by the three different techniques, water saturation graphs were produced to observe the symbolic difference of Archie's parameter and its relevant impact on water saturation values. The difference in water saturation values can be primarily attributed to showing the uncertainty level of Archie's parameters, mainly in carbonate and sandstone rock samples. It is obvious that the accuracy of Archie's parameters has a profound impact on the calculated water saturation values in carbonate sandstone reservoirs due to regions of high stress reducing electrical conduction resulting from the raised electrical heterogeneity of the heterogeneous carbonate core samples. Due to the unrealistic assumptions involved in the conventional method, it is better to use either the CAPE or 3D method to accurately determine Archie's parameters in heterogeneous as well as homogeneous reservoirs. © 2017 Sinopec Geophysical Research Institute.